Coping with discrepancies: implications of career guidance and counselling for migrants' social inclusion in Finland and Sweden - Alessandra Aldrovandi; Mira Kalalahti; Åsa Sundelin (Taylor & Francis Group, 2024)
Career guidance and counselling (CGC) plays an important role in the 'egalitarian tradition' of the Nordic countries' perspective of education, since it aims to support all students in developing skills and knowledge to access further education and the labour market. Inspired by the critical institutionalism approach and focusing on education aimed at migrant students, this article explores the strategies that school actors implement to cope with the discrepancies between CGC policy and practice by analysing two cases: one in adult vocational education and training in Finland and the other in the Language Introduction Programme in Sweden. The ecological framework facilitates an understanding of the complex policy - practice dynamics within the local learning ecologies while also opening up a discussion on their implications for migrant students' opportunities for social inclusion. The findings show how the shortcomings of the policy - practice relationship affect teachers' and counsellors' work, and how students consequently may end up relying on self and peer support.